Symptoms of posttraumatic stress, anxiety, and depression, along with their associated factors, among Eritrean refugees in Dabat town, northwest Ethiopia, 2023 - Mihret Melese; Wudneh Simegn; Dereje Esubalew; Liknaw Workie Limenh; Wondim Ayenew; Gashaw Sisay Chanie; Abdulwase Mohammed Seid; Alemante Tafese Beyna; Melese Legesse Mitku; Asefa Kebad Mengesha; Yibeltal Yismaw Gela (BMC Psychology, 2024)
Abstract Background Refugee populations are forcibly displaced from their homes as a consequence of natural disasters and armed conflicts. Eritreans, initially displaced to the Maiayni camp within the Tigray region, have faced further relocation to Dabat town due to the conflict between the Tigray People Liberation Front (TPLF) and Ethiopian government forces. Subsequently, another conflict has arisen between the Amhara Popular Force (Fano) and Ethiopian government forces in Dabat town, disrupting its stability. These collective challenges in the new environment may contribute to the development of symptoms such as posttraumatic stress disorder (PTSD), anxiety, and depression. Currently, there is a lack of available data on these symptoms and their associated variables in Dabat Town. Thus, the objective of this study was to assess the prevalence of PTSD, anxiety, and depression symptoms, along with associated factors, among Eritrean refugees in Dabat town, northwest Ethiopia. This will provide significant evidence for developing and implementing mental health intervention strategies that specifically address the particular difficulties faced by refugees. Method A community-based cross-sectional study was carried out from July 25 to September 30, 2023, in the Eritrean refugee camp in Dabat town. A systematic random sampling method was employed to select a total of 399 Eritrean refugees with 100 response rate. Data were collected using the standard validated Depression, Anxiety, and Stress Scale (DASS-21) questionnaire, which included socio-demographic characteristics. Summary statistics such as frequency and proportion were utilized to present the data in tables and figures. Binary logistic regression was employed to identify associated factors, and variables with a p-value (p ≤ 0.05) were considered statistically significant factors. Result The findings of this study indicated that 45% (95% CI: 35.6-48.23), 33.6% (95% CI: 31.66–37.45), and 37.3% (95% CI: 35.56–40.34) of the participants had symptoms of depression, anxiety, and PTSD, respectively. Sex, age, employment status, lack of food or water, experience of torture or beating, and imprisonment emerged as statistically significant predictors of depression. Employment status, murder of family or friends, rape or sexual abuse, torture or beating, and lack of housing or shelter were statistically significantly associated with anxiety. PTSD was found to be significantly associated with sex, length of stay at the refugee camp, lack of housing, shelter, food, or water, experience of rape or sexual abuse, abduction, employment status, and murder of family or friends. Conclusions and recommendation The results of this study revealed that more than one-third of Eritreans living in the refugee camp in Dabat town had symptoms of PTSD, anxiety, and depression. This prevalence is higher than the previously reported studies. Various factors, including age, gender, monthly income, unemployment, experiences of rape or sexual abuse, witnessing the murder of family or friends, being torched or beaten, imprisonment, and deprivation of basic needs such as food, shelter, and water, were identified as contributors to the development of depression, anxiety, and PTSD. This research underscores the need for both governmental and non-governmental organizations to secure the provision of essential necessities such as food, clean water, shelter, clothing, and education. This study also suggested that Eritrean refugees be legally protected from rape, sexual abuse, arson, detention without cause, and kidnapping. Moreover, the study calls for health service providers to develop a mental health intervention plan and implement strategies to deliver mental health services at healthcare facilities for Eritrean refugees in the Dabat town Eritrean refugee camp.